2009
DOI: 10.1111/j.1540-6210.2009.02034.x
|View full text |Cite
|
Sign up to set email alerts
|

Are State Marriage Initiatives Having an Eff ect ?An Initial Exploration of the Impact on Divorce and Childhood Poverty Rates

Abstract: To our knowledge … this analysis provides the fi rst macro-level test of state policies and programs intended to promote healthy marriages. Th e central question addressed by this article is the eff ect of state-level marriage initiatives on divorce and childhood poverty rates. State divorce rates have been problematic for researchers because of variation across states in the way they are compiled. Th is research takes a diff erent approach, measuring instead the prevalence of divorce rather than the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…One of the few significant findings to emerge from their study was a negative association between state support for MRE and divorce rates. And the Kirkham and Ford () study found that HMI activity in 11 high‐activity states was associated with declines in the percentage of divorced adults in the population of those states. But we could not replicate this potential effect on divorce with our data, although our focus was on direct funding of HMI services, whereas their focus was on legislation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few significant findings to emerge from their study was a negative association between state support for MRE and divorce rates. And the Kirkham and Ford () study found that HMI activity in 11 high‐activity states was associated with declines in the percentage of divorced adults in the population of those states. But we could not replicate this potential effect on divorce with our data, although our focus was on direct funding of HMI services, whereas their focus was on legislation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is highly likely that the times and places where more money is spent to promote healthy marriages are systematically different from other times and places. For example, Kickham and Ford () found that the states most active in healthy marriage initiatives tended to be Southern states and states with higher proportions of Blacks and higher divorce rates than other states. Those states might also have systematically different culture, politics, and economic changes during any particular period that could confound the interpretation of any changes in marriages and other outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research on marriage promotion has focused on the extent to which interventions increase the quantity and quality of marriages themselves. There are many good reviews of that evidence (e.g., Hawkins, Blanchard, Baldwin, & Fawcett, ; Kickham & Ford, ; Stanley, Markman, Rhoads, & Prentice, 2010), but that is not our primary purpose here. We begin by describing the evidence that has most often been used to argue that marriage is generally beneficial to the married people, their children, and to society.…”
Section: Critical Review Of Marriage Promotion Researchmentioning
confidence: 99%
See 2 more Smart Citations